First‐principles lattice dynamics and Raman scattering in ionic conductor β‐Ag2S. Issue 10 (11th August 2016) - Alekperov, Oktay; Jahangirli, Zakir; Paucar, Raul
Abstract : The phonon structure of the silver sulfide Ag2 S was investigated, experimentally using Raman spectroscopy, and theoretically using the density‐functional perturbation theory for the first time. Seven Raman‐active modes were observed and identified at 23, 39, 42, 44, 62, 65, and 243 cm −1 . Symmetry assignments of all the vibrational modes were derived from considerations of point group symmetry. The phonon band structure and the relative Raman intensities were also investigated by ab initio calculations and compared with the experimental data. The temperature, laser power, and illumination time dependencies of frequency, linewidth, and intensity of the Raman‐active modes are discussed. In the Raman spectra at higher frequencies 1300–1700 cm −1, additional broad Raman modes observed in all samples at higher laser powers 8–10 mW were ascribed to luminescence from β‐Ag2 S. The phonon and Raman spectra of the β‐Ag2 S provide a useful insight into the β‐Ag2 S → α‐Ag2 S phase transition. Finally, calculated infrared vibrational mode frequencies were compared with measured infrared mode frequencies.